Phase I/II study of the novel proteasome inhibitor delanzomib (CEP-18770) for relapsed and refractory multiple myeloma. Issue 8 (3rd August 2017) - Vogl, Dan T.; Martin, Thomas G.; Vij, Ravi; Hari, Parameswaran; Mikhael, Joseph R.; Siegel, David; Wu, Ka Lung; Delforge, Michel; Gasparetto, Cristina
Abstract: Delanzomib (CEP-18770), a reversible P2 threonine boronic acid proteasome (β5/β1 subunits) inhibitor that showed promising anti-myeloma effects in preclinical studies, was investigated in a single-agent multicenter phase I/II study in patients with relapsed/refractory myeloma. Sixty-one patients (17 during dose escalation; 44 in the expansion cohort) received delanzomib on days 1, 8, and 15 in 28-d cycles; 47 received the maximum tolerated dose (MTD), 2.1 mg/m 2 . Dose-limiting toxicities (DLTs) at 2.4 mg/m 2 were rash and thrombocytopenia. At the MTD, the most prominent adverse events were nausea, vomiting, anorexia, fatigue, and pyrexia; grade 3/4 thrombocytopenia and neutropenia occurred in 53 and 23% of patients, respectively. Peripheral neuropathy (21%) was limited to grades 1/2. At the MTD, 26 patients (55%) had stable disease and four (9%) had a partial response (PR). Median time to progression (TTP) was 2.5 months across the cohort. Based upon the efficacy results, development of delanzomib for myeloma was discontinued.